Studies of Atmospheric Parameters during SW Monsoon Period Associated with Severe Cyclone Aila and Lightning Occurrence over Ranchi Region. (7th August 2012) - Srivastava, Abhay; Kumar, Manoj; Dwivedi, Arun K.
Abstract : A number of events are happening every time in the atmosphere in which much of them are randomly generated. Parameters are varying daily like temperature, humidity, electric field, and wind speed. Variation on surface layer parameters, events thunderstorms, earthquake, volcanoes, cyclone, tsunami, and so forth are occurring. Study and correlation between surface layer parameter and occurrence are greatly required in current research scenario. A comparative study about atmospheric parameters has been done just after the Aila; in the day when lightning occurred and correlation coefficients between these parameters are observed.